Where Terror Lies: Misrepresentation of Extremist Attitudes and Terrorist Attacks in the Sahel - Finkel, Steven E. (Terrorism and political violence, 2023)
Researchers have commonly treated misrepresentations in survey responses as an impediment to the accurate measurement of a variable or construct of substantive importance. This study builds on that approach and considers whether misreporting bias regarding support for violent extremism—both under- and over-reporting—may then have consequences for how terrorist violence itself unfolds. Using data from nearly 4,000 respondents in thirty-five communes in Burkina Faso, Chad, and Niger collected just prior to a recent wave of terrorist attacks, we find that communes where individuals under-report their true support for violent extremism—as measured with unobtrusive experimental methods—have a greater probability of experiencing subsequent Islamist attacks, controlling for socio-demographic characteristics of the commune, country-level proximity effects, and other time-varying factors. The findings raise important considerations regarding the measurement of extremist support, and they suggest a new tool for identifying communities potentially susceptible to terrorist violence.